Extracellular HSP90α Interacts With ER Stress to Promote Fibroblasts Activation Through PI3K/AKT Pathway in Pulmonary Fibrosis - Zhang, Jinming; Zhong, Wenshan; Liu, Yuanyuan; Chen, Weimou; Lu, Ye; Zeng, Zhaojin; Qiao, Yujie; Huang, Haohua; Wan, Xuan; Li, Wei; Meng, Xiaojing; Zou, Fei; et al. (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis is characterized by alveolar epithelial cell injury, lung fibroblast proliferation, differentiation, and extracellular matrix (ECM) deposition. Our previous study indicated that extracellular HSP90α (eHSP90α) promotes pulmonary fibrosis by activating the MAPK signaling pathway. Thus, treatment with 1G6-D7 (a selective HSP90α monoclonal antibody) to antagonize eHSP90α could effectively ameliorate fibrosis. This study aimed to elucidate the mechanism underlying the effects of eHSP90α in pulmonary fibrosis by focusing on its link with endoplasmic reticulum (ER) stress. Our results showed that eHSP90α promoted lung fibroblast differentiation by activating ER stress. Treatment with the ER stress inhibitor tauroursodeoxycholate (TUDCA) or glucose-regulated protein 78 kDa (GRP78) depletion significantly abrogated the effect of eHSP90α on ER stress and fibroblast activation. In addition, eHSP90α induced ER stress in fibroblasts via the phosphoinositide-4,5-bisphosphate 3-kinase (PI3K)-protein kinase B (AKT) signaling pathway, which could be blocked by the PI3K/AKT inhibitor LY294002, and blockade of eHSP90α by 1G6-D7 markedly inhibited ER stress in the model, indicating preventive and therapeutic applications. Intriguingly, we observed that TUDCA effectively reduced the secretion of eHSP90α in vitro and in vivo. In conclusion, this study shows that the interaction between eHSP90α and ER stress plays a crucial role in pulmonary fibrosis, indicating a positive feedback in lung fibroblasts. Targeting eHSP90α and alleviating fibroblast ER stress may be promising therapeutic approaches for pulmonary fibrosis.